The Epistemic Value of Deep Disagreements - Lougheed, Kirk (Informal Logic)

(untitled) (Informal Logic, 2018)
In the epistemology of disagreement literature an underdeveloped argument defending the claim that an agent need not conciliate when she becomes aware of epistemic peer disagreement is based on the idea that there are epistemic benefits to be gained from disagreement. Such benefits are unobtainable if an agent conciliates in the face of peer disagreement. I argue that there are good reasons to embrace this line of argument at least in inquiry-related contexts. In argumentation theory a deep disagreement occurs when there is a disagreement between fundamental frameworks. According to Robert J. Fogelin disagreements between fundamental frameworks are not susceptible to rational resolution. Instead of evaluating this claim I argue that deep disagreements can lead to epistemic benefits, at least when inquiry is in view. Whether rational resolution is possible in cases of deep disagreements, their existence turns out to be epistemically beneficial. I conclude by examining whether this line of argument can be taken beyond research-related contexts.